Immune-related gene-based model predicts the survival of colorectal carcinoma and reflected various biological statuses - Kang, Zhengchun; Chen, Bingchen; Ma, Xiuzhu; Yan, Feihu; Wang, Zhen (Frontiers in Molecular Biosciences, 2023)
Prognosis of colorectal cancer (CRC) varies due to complex genetic-microenviromental interaction, and multiple genes based prognostic model have been highlighted. In this work, immune-related genes' expression based model was developed, scores of each sample were calculated. The high-score samples have significantly longer survival (overall survival and progression-free survival) period than these with low score, which was validated across seven datasets containing 1325 samples (GSE17536 (N=115), GSE17537 (N=55), GSE33113 (N=90), GSE37892 (N=130), GSE38832 (N=74), GSE39582 (N=481), TCGA (N=380)). The score is significantly associated with clinical indicators including age and stage, and associated with PD-1/PD-L1 gene expression. Also, high score samples have significantly higher APC and lower MUC5B mutation rate. The high score samples have more immune infiltration (including CD4+, CD8+ T cell, M1/M2 macrophage and NK cells). Enriched pathway analyses showed that cancer-related pathways including immune-related pathways were significantly activated in high score samples, and some drugs have significantly lower IC50 than these with low score. Collectively, the model developed based on immune-related genes is robust and reflected various status of CRC, and may be a potential clinical indicator.